THE DEVELOPMENT OF E-LKPD (STUDENT WORKSHEET) IN SCIENCE LEARNING IN GRADE V AT SIEM PRIMARY SCHOOL - Lili Kasmini; Mardhatillah; Haris Munandar; Mukhroji (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
During the Covid-19 pandemic, schools did many ways to keep the learning going, such as implementing online learning using learning tools that were also in the form of online, one of which was the E-LKPD or digital-based student worksheets. E-LKPD is a student work guide to make it easier for students to carry out learning activities electronically seen on desktop computers, notebooks, smartphones, and mobile phones. This study aimed to determine the development of E-LKPD in science learning at grade V of Siem Primary School. The type of research used is Research and Development or R & D research, using the ADDIE development design. Instruments or tools used for data collection are validation sheets and questionnaires. This validation sheet contains responses or opinions regarding E-LKPD, making it easier for validators to provide responses and assessments. Based on the results obtained, the development of E-LKPD has reached the very feasible category with an average score of 3.66. This assessmen (Tempatpenampung2)t includes aspects of feasibility, language, presentation, and graphics. Thus, the development of the E-LKPD shows that the criteria are very suitable for use in learning. Based on the results of the student questionnaire, 13 students out of a total of 16 people gave a response that strongly agreed on the developed E-LKPD, or with a percentage reaching 81.25%. Abstrak Di masa pandemi Covid-19, sekolah melakukan banyak cara agar pembelajaran tetap berjalan, seperti menerapkan pembelajaran daring menggunakan perangkat pembelajaran yang juga berupa daring, salah satunya E-LKPD atau lembar kerja siswa berbasis digital. E-LKPD merupakan pedoman karya siswa untuk memudahkan siswa dalam melakukan kegiatan pembelajaran secara elektronik yang terlihat di komputer desktop, notebook, smartphone, dan telepon genggam. Penelitian ini bertujuan untuk mengetahui perkembangan E-LKPD dalam pembelajaran IPA di kelas V SD Siem. Jenis penelitian yang digunakan adalah Penelitian dan Pengembangan atau penelitian R&D, menggunakan desain pengembangan ADDIE. Instrumen atau alat yang digunakan untuk pengumpulan data adalah lembar validasi dan angket. Lembar validasi ini berisi tanggapan atau pendapat terkait E-LKPD, sehingga memudahkan validator dalam memberikan tanggapan dan penilaian. Kuesioner berisi beberapa pertanyaan yang diajukan kepada mahasiswa untuk mengetahui uji coba pengembangan E-LKPD dengan mengisi kuesioner berdasarkan pendapat pribadi. Berdasarkan hasil yang diperoleh, pengembangan E-LKPD telah mencapai kategori sangat layak dengan skor rata-rata 3,66. Penilaian ini mencakup aspek kelayakan, bahasa, presentasi, dan grafis. Dengan demikian, pengembangan E-LKPD menunjukkan bahwa kriteria tersebut sangat cocok digunakan dalam pembelajaran. Berdasarkan hasil angket siswa, 13 siswa dari total 16 orang memberikan tanggapan yang sangat setuju dengan E-LKPD yang dikembangkan, atau dengan persentase mencapai 81,25%.